2021
DOI: 10.3846/est.2020.14555
|View full text |Cite
|
Sign up to set email alerts
|

The Engineering Method for Unifying Ground Floor Slab Settlements

Abstract: For industrial buildings and logistics centres truck lifts are usually used. Therefore, there are special requirements for flatness tolerance of ground floor. The ground floor settlements differences in selected distances are limited. The article reviews the behaviour of soils and the importance of the actual behaviour assessment of soils during the design of floor slab on elastic subgrade. Particular attention is given to the behaviour of floor slab areas above pile foundations that support the building’s col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Apart from that, negative skin friction (NSF) is also an indicator [13]. Settlement is another indicator of structural safety [14], [15], [16]. It has been revealed that the difference between the depth of the foundation plan and its implementation in the field on sandy soils has significant variations in various locations worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from that, negative skin friction (NSF) is also an indicator [13]. Settlement is another indicator of structural safety [14], [15], [16]. It has been revealed that the difference between the depth of the foundation plan and its implementation in the field on sandy soils has significant variations in various locations worldwide.…”
Section: Introductionmentioning
confidence: 99%